The Hidden Patients North African Women in French Colonial Psychiatry - Salouâ Studer, Nina (Zürcher Beiträge zur Geschichtswissenschaft, 2015)
This English-language study is dedicated to questions of gender research and the history of medicine in colonial North Africa. It shows that French psychiatrists described "normal" and "abnormal" behaviors of the colonized in the Maghreb and compared them to those of Europeans who had diagnosed them with "abnormality."